The Analysis of Development Natural gas-based Petrochemical Industry in Teluk Bintuni Regency - Dedy Setyo Oetomo; Rizky Fajar Ramdhani (Bandung State Polytechnic (Politeknik Negeri Bandung), 2021)
ABSTRACT The petrochemical industry, especially the petrochemical industry in Teluk Bintuni Regency, West Papua Province, is an industry engaged in natural gas processing by considering the needs of the Upstream Plastic Product Industry Market and its use in supporting human activities. It is hoped that the integration of the upstream-downstream industry can build a strong supply chain. This is in line with the application of industry 4.0 according to the roadmap of Making Indonesia 4.0, which aims to increase the competitiveness of the national industry in the global arena. Examples of upstream petrochemical industry products include methanol, ethylene, propylene, butadiene, benzene, toluene, xylene, coproduct fuels, petrol pyrolysis, fuel oil pyrolysis, raffinate, and C4 mixtures. The analysis developed is using an Industrial Tree Model and porter's value chain analysis and supply chain analysis. The results of this research are seven points.